Effect of Non-Rebreathing Mask Oxygenation and 30-Degree Head-Up Positioning on Consciousness and Hemodynamics in Pulmonary Tuberculosis Patients: A Case Study - Febriyanti, Febriyanti; Thalib, Abdul Herman Syah (Genius Journal, 2025)
Introduction: Tuberculosis is transmitted by bacteria called Mycrobacterium tuberculosis and is lassified as an infectious disease. Transmission occurs when an individual inhales airborne particles containing sputum droplets from a tuberculosis sufferer. Objective: To determine the level of consciousness and hemodynamic changes in pulmonary tuberculosis patients before and after the implementation of non-rebreathing mask oxygenation and a 30 degree head up position. Method: The strategy applied in compiling this paper is a case study method used to describe the situation descriptively in accordance with the topic of discussion, namely the Implementation of Non-Rebreathing Mask Oxygenation and 30° Head Up Position on the Level of Consciousness and Hemodynamic Changes in Pulmonary Tuberculosis Patients. Result: Before administering non-rebreathing mask oxygenation and 30-degree head-up position, Mr. S experienced a decreased level of consciousness with a GCS of 8 and shortness of breath. After administering non-rebreathing mask oxygenation and 30-degree head-up position for 3 days, Mr. S's level of consciousness increased with a GCS of 10. Conclusion: Based on the author's observations in the implementation of the case study related to "Implementation of Non-Rebreathing Mask Oxygenation and 30° Head Up Position on the Level of Consciousness and Hemodynamic Changes in Pulmonary Tuberculosis Patients" for 3 days starting from April 16-18, 2025 at Faisal Islamic Hospital, Makassar, it can be concluded that after the Implementation of Non-Rebreathing Mask Oxygenation and 30° Head Up Position on the Level of Consciousness and Hemodynamic Changes in Pulmonary Tuberculosis Patients, awareness and hemodynamic changes can be increased.